Java知识分享网 - 轻松学习从此开始!    

Java知识分享网

Java1234官方群25:java1234官方群17
Java1234官方群25:838462530
        
SpringBoot+SpringSecurity+Vue+ElementPlus权限系统实战课程 震撼发布        

最新Java全栈就业实战课程(免费)

springcloud分布式电商秒杀实战课程

IDEA永久激活

66套java实战课程无套路领取

锋哥开始收Java学员啦!

Python学习路线图

锋哥开始收Java学员啦!
当前位置: 主页 > Java文档 > Java基础相关 >

数据结构与算法分析(Java语言描述)习题答案(第三版) PDF 下载


分享到:
时间:2021-06-26 08:17来源:http://www.java1234.com 作者:转载  侵权举报
数据结构与算法分析(Java语言描述)习题答案(第三版) PDF 下载
失效链接处理
数据结构与算法分析(Java语言描述)习题答案(第三版) PDF 下载


本站整理下载:
提取码:qiza 
 
 
相关截图:
 
主要内容:
Introduction
 
1.4The general way to do this is to write a procedure with heading
 
void processFile( String fileName );
 
which opens fileName, does whatever processing is needed, and then closes it. If a line of the form
 
#include SomeFile
 
is detected, then the call
 
processFile( SomeFile );
 
is made recursively. Self-referential includes can be detected by keeping a list of files for which a call to
 
processFile has not yet terminated, and checking this list before making a new call to processFile.
 
1.5public static int ones( int n )
{
if( n < 2 ) return n;
return n % 2 + ones( n / 2 );
}
 
1.7(a) The proof is by induction. The theorem is clearly true for 0 < X  1, since it is true for X = 1, and for X < 1, log X is negative. It is also easy to see that the theorem holds for 1 < X  2, since it is true for X = 2, and for X < 2, log X is at most 1. Suppose the theorem is true for p < X  2p (where p is a positive integer), and consider any 2p < Y  4p (p  1). Then log Y = 1 + log(Y/2)< 1 + Y/2 < Y/2 + Y/2  Y, where the first inequality follows by the inductive hypothesis.
(b) Let 2X = A. Then AB = (2X)B = 2XB. Thus log AB = XB. Since X = log A, the theorem is proved.
 
1.8(a) The sum is 4/3 and follows directly from the formula.
 
 
(b)
 
S  1  2  3 
 
Subtracting the first equation from the second gives
 
4 42 43
 
 
3S  1  1  2 
4 42
 
. By part (a), 3S = 4/3 so S = 4/9.
 
 
 
(c)
 
S  1  4  9 
 
Subtracting the first equation from the second gives
 
4 42 43
 
3S  1   3   5   7  Rewriting, we get 3S  2 i   1 . Thus 3S = 2(4/9) + 4/3 = 20/9. Thus S =
 
 
4 42 43
 
i0 4
 
i0 4
 
20/27.
 
(d) Let SN =  iN . Follow the same method as in parts (a) – (c) to obtain a formula for SN in terms of SN–1,
i0
 
SN–2,..., S0 and solve the recurrence. Solving the recurrence is very difficult.
 
N N  N / 21
 
1.9
 
 1   1 
 
 1  ln N  ln N / 2  ln 2.
 
i N / 2 i1
 
i1
 
 
1.10 24 = 16  1 (mod 5). (24)25  125 (mod 5). Thus 2100  1 (mod 5).
 
1.11 (a) Proof is by induction. The statement is clearly true for N = 1 and N = 2. Assume true for N = 1, 2, ... , k.
 
k  1 k
 
Then
 
 Fi   Fi  Fk 1. By the induction hypothesis, the value of the sum on the right is Fk+2 – 2 + Fk+1 =
 
i1 i1
 
Fk+3 – 2, where the latter equality follows from the definition of the Fibonacci numbers. This proves the claim for N = k + 1, and hence for all N.
(b)As in the text, the proof is by induction. Observe that  + 1 = 2. This implies that  –1 +  –2 = 1. For N = 1 and N = 2, the statement is true. Assume the claim is true for N = 1, 2, ... , k.
Fk 1  Fk  Fk 1
 
by the definition, and we can use the inductive hypothesis on the right-hand side, obtaining
 
Fk 1   k    k1
 1 k 1   2 k 1
Fk 1  ( 1   2 ) k 1   k 1
 
and proving the theorem.
 
(c)See any of the advanced math references at the end of the chapter. The derivation involves the use of generating functions.
N N N
1.12 (a) (2i  1)  2i  1 = N(N + 1) – N = N2.
 
i1
 
i1
 
i1
 
 
(b) The easiest way to prove this is by induction. The case N = 1 is trivial. Otherwise,


 
 
------分隔线----------------------------

锋哥公众号


锋哥微信


关注公众号
【Java资料站】
回复 666
获取 
66套java
从菜鸡到大神
项目实战课程

锋哥推荐